2006
DOI: 10.1257/000282806777212620
|View full text |Cite
|
Sign up to set email alerts
|

The Polarization of the U.S. Labor Market

Abstract: This paper analyzes a marked change in the evolution of the U.S. wage structure over the past fifteen years: divergent trends in upper-tail (90/50) and lower-tail (50/10) wage inequality. We document that wage inequality in the top half of distribution has displayed an unchecked and rather smooth secular rise for the last 25 years (since 1980). Wage inequality in the bottom half of the distribution also grew rapidly from 1979 to 1987, but it has ceased growing (and for some measures actually narrowed) since th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
391
3
27

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,160 publications
(482 citation statements)
references
References 11 publications
22
391
3
27
Order By: Relevance
“…The literature on employment in OECD economies has recently devoted a lot of attention to the polarisation of employment (Autor et al, 2006;Goos et al, 2009). The latter refers to the changes occurring in employment patterns whereby the share of occupations at both ends of the skill distribution (low-skilled and high-skilled jobs) increases, while employment in the middle of the distribution (midskilled jobs) declines.…”
Section: Routine Intensity Automatisation and Offshorability: A Briementioning
confidence: 99%
See 1 more Smart Citation
“…The literature on employment in OECD economies has recently devoted a lot of attention to the polarisation of employment (Autor et al, 2006;Goos et al, 2009). The latter refers to the changes occurring in employment patterns whereby the share of occupations at both ends of the skill distribution (low-skilled and high-skilled jobs) increases, while employment in the middle of the distribution (midskilled jobs) declines.…”
Section: Routine Intensity Automatisation and Offshorability: A Briementioning
confidence: 99%
“…This same classification was adopted as such in a number of later studies, or further elaborated in a tripartite classification (e.g. Autor et al, 2006 andAutor et al, 2013a andAutor and Dorn, 2013;Goos et al, 2009 and2014).…”
Section: Routine Intensity Automatisation and Offshorability: A Briementioning
confidence: 99%
“…Nolan and Slater (2010) have shown that growth in employment in higher level professional and technical occupations in the UK has coincided with an expansion of manual service occupations requiring low or intermediate skills, resulting in an 'hour-glass' economy. Similarly, analyses of the UK, US, West Germany and other OECD countries (see Autor et al, 2006;Goos and Manning, 2007;Goos et al, 2009Goos et al, , 2014Spitz-Oener, 2006) have found that a 'polarisation' of work has occurred. Goos and Manning (pace Autor et al, 2003) note that the scope for capital substitution that is key to the 'skill-biased technological change' thesis is limited in respect of low-paid non-routine manual work (such as cleaning) and more likely to affect routine administrative work in the middle of the earnings distribution (e.g.…”
Section: Skills Occupations and Young Workersmentioning
confidence: 97%
“…Some analysts suggest that this experience of "jobless recovery" since the 1990s is the result of the increased diffusion of information technology throughout the economy, as higher levels of productivity have enabled companies to produce more goods and services with fewer people and more machinery, robots, and computers (Autor, Katz, and Kearney 2006;Brynjolfsson and McAfee 2011). This argument, however, ignores the widespread evidence, both in the United States and abroad, that the overall impact of technology on job and wage levels is indeterminate-that it depends on a variety of other factors, including trade patterns, exchange rates, and education policies, that shape the overall relationship between technology diffusion and job creation (Bogliacino and Vivarelli 2010;C.…”
Section: The Jobs Crisismentioning
confidence: 99%